Emerging Technologies for 3D Video: Creation, Coding, Transmission and Rendering - Cagnazzo, Marco (John Wiley & Sons, 2013)
With the expectation of greatly enhanced user experience, 3D video is widely perceived as the next major advancement in video technology. In order to fulfil the expectation of enhanced user experience, 3D video calls for new technologies addressing efficient content creation, representation/coding, transmission and display.